Peningkatan Kualitas Layanan Penyedia Layanan Logistik Berdasarkan Integrasi SERVQUAL dan QFD - Ramli Murgani; Sawarni Hasibuan (Universitas Katolik Parahyangan, 2022)
This study aims to find the causes of customer dissatisfaction and its implications for logistics service provider (LSP) operations management by improving the quality of customer service. This research is a case study on Pusat Logistik Berikat (PLB), a logistics service provider based in Cilincing, Indonesia. Qualitative and quantitative methods were used with the Delphi method for expert validation. Data were collected during the covid-19 pandemic using questionnaires distributed to a limited sample of 50 PLB customers and semi-structured interviews to deepen information related to site observations. The 5-dimensional service quality (SERVQUAL) instrument was validated using 40 completed questionnaires used as primary data, resulting in 33 valid attributes. GAP analysis found 30 attributes have low performance, and reliability, assurance, tangibles, responsiveness, and empathy contribute to customer satisfaction. Empathy was the priority for improving the quality of employees. Six attributes based on importance performance analysis (IPA) were identified as the voice of customer (VOC). Based on QFD evaluation, it was found that for the most critical professional improving the quality of customer service is performance as an added value for the logistics process, and the lowest is the fast response from the customer service team. Highest technical requirements: cycle time and lowest stock out. The technical implications of the SERVQUAL and QFD approaches can be used to increase customer satisfaction through improving the quality of human resources and procurement management.